Criminal Responsibilities Or Political Partners As Corporations In Corruption Criminal Action And Money Laundering Criminal Acts (Deposisi: Jurnal Publikasi Ilmu Hukum, 2023)
The existence of political parties plays a strategic role in the development of democracy and the nation is faced with a number of issues that create a negative impression on these organs, some of which include; first, the problem of involvement of political parties in various cases of corruption and money laundering crimes that have an impact on the fall of public image and trust in the organization; second, the problem of pro and contra accountability of political parties involved in cases of corruption and criminal acts of money laundering before the law; and third, the issue of imposing criminal sanctions on political parties as the subject of corporate offenses known in corruption and money laundering. This research belongs to the typology of juridical normative legal research with secondary data types in the form of primary, secondary and tertiary legal materials. The approach taken includes the comparison, conceptual, statutory, and philosophical approaches, and analyzed descriptively qualitatively through literature. The results of the study show that; first, the justification of political parties as corporations in criminal acts of corruption and criminal acts of money laundering can be seen in five basic perspectives, namely philosophical foundation, juridical basis, historical basis, sociological basis, and political foundation of criminal law; second, the ideal concept of political party punishment as a corporation is carried out with a reconceptualization of the subject of corporate delictions in the affirmation of two types of corporations, namely corporations in the form of private and special corporations or in the form of public with different provisions on punishment arrangements. The need for an amendment to some provisions of the Corruption Law and the TPPU Law related to corporations in accommodating the two types of corporations into a forum for the implementation of ideas, of course issuing a law that contains specific provisions regarding special corporate punishment can be the answer to a myriad of issues regarding criminalization